HERBAL MEDICINES AND MUSCLE PERFORMANCE: RECENT EVIDENCE ON MUSCLE GAIN AND TESTOSTERONE IN ACTIVE MEN (REMUNOM, 2026)
The use of herbal remedies as a natural alternative to anabolic steroids has gained prominence in the field of sports nutrition, driven by the pursuit of improved physical performance and body composition. However, the efficacy and safety of these substances still require consistent scientific evidence. This study aimed to review recent evidence on the main commercially available herbal remedies that increase testosterone and muscle mass, namely Tribulus terrestris, Eurycoma longifolia, Withania somnifera, Mucuna pruriens, Fadogia agrestis, and Bulbine natalenses. This is a systematic literature review conducted in the databases “PubMed”, “Scopus”, “Web of Science”, and “Google Scholar”. Eleven articles were selected, both in English and Portuguese, considering studies from January 2020 to October 2025, with samples composed of young, healthy, and physically active men. The results indicated that Withania somnifera showed the most consistent effects, such as cortisol reduction, improved strength and muscle recovery, but without a significant increase in testosterone. Eurycoma longifolia showed benefits in relation to well-being and stress, but without a relevant hormonal impact. Tribulus terrestris, Mucuna pruriens, Fadogia agrestis and Bulbine natalenses had limited efficacy and potential risks of liver and kidney toxicity. It is concluded that current studies are still very limited, not showing significant results on increasing testosterone and muscle mass gain. Therefore, the use of this substance should be done with caution and under professional guidance.